Export credit insurance backed by the State Treasury vs. capital adequacy of banks. Analysis of the possibility of using an insurance policy of KUKE SA as a recognised agreement on the unfunded credit protection for the exposition constituting the officia (Economic and Political Thought, 2018)
The article discusses the use of export insurance backed by the StateTreasury as a recognized credit risk mitigation technique under Regulation575/2013, concerning the exposure to risk of export credit offered by thebanking sector. Recognition of the insurance policy of KUKE SA [ExportCredit Insurance Corporation], a Polish ECA, as such a technique is oneof the conditions for appropriate determination of the risk weight for theestimation of the capital adequacy ratio of the bank. The issue is of greatimportance for higher engagement of the domestic banking sector in providingexport credits and supporting the domestic companies entering foreignmarkets by increased involvement in financing companies importing productsand services from Poland.In order to illustrate the issues in more detail, the article also analysesmain international regulations requirements that need to be taken into accountin the context of subsidizing export activity as well as main principles ofthe officially supported export credits with special focus on the complianceof unfunded credit protection provided by KUKE SA with CRR.The article does not deal with the issue referred to in Article 194 par. 5in conjunction with Article 201 par. 1 Capital Requirements Regulation concerningthe official provider of unfunded credit protection and requirementsthat a provider of unfunded credit protection should fulfil to be a recognisedone. The analysis of the above issue will be discussed in a separate article.Attention must be also drawn to the fact that the considerations presentedin the article concern only an insurance policy and not insurance collateralapplied in foreign trade for the needs of the protection of payment by foreigntrade partners in short-term transactions, which will also be discussed ina separate article.
Keywords: credits, insurance, State Treasury, risk, banks